Activities of nutrition education: An experience with workers ofa company of eucalyptus plantation and processing. - Moreira Souza, Elaine de Fátima; Ferreira de Almeida, Martha Elisa; Rodrigues Carvalho Cruz, Nilcemar (Guará Journal, 2025)
The objective of the study was to promote nutritional education initiatives to encourage appropriate health practices. The study was conducted at a eucalyptus plantation company, including its outsourced departments, located in several cities in Minas Gerais. 4,389 employees and their spouses participated in the project. Lectures, theater, film, group activities, booklets, and stands were used. The study concluded that the development of this study helped employees realize that various inadequate health practices are determinants of their health status.